THE EFFECTIVENESS OF ACTIVE LEARNING IN THE ACHIEVEMENT OF CHEMISTRY AND MOTIVATION AMONG INTERMEDIATE THIRD-GRADE STUDENTS - Hiam Ghaieb Hussein, Afraa Sabri Mohammed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to show the effectiveness of active learning in increasing the motivation and achievement of third - grade intermediate students in the section of chemistry, the research sample consists of (40) students divided into two equal groups, one experimental and the other control, and the research tools consisted of an achievement test of the multiple choice type, and the motivation scale among students, and after statistical treatment, the results of the research indicated that there is a statistically significant difference between the experimental and control group in achievement and the motivation scale for the benefit of the experimental group, and in light of the results, the researchers recommended paying attention to develop the achievement and motivation of students simultaneously since each of them can serve the other and the need to consult behavior students and their rush to pay attention to the educational position .